Distributed Applications and Interoperable Systems : 15th IFIP WG 6.1 International Conference, DAIS 2015, Held as Part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, Grenoble, France, June 2-4, 2015, Proceedings - Bessani, Alysson; Bouchenak, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 15th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2015, held as part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, in Grenoble, France, in June 2015. The 14 full papers and 3 short papers presented in this volume were carefully reviewed and selected from 44 submissions. They deal with topics such as fault tolerance, privacy, resource management, social recommenders and cloud systems.
Fluidify: Decentralized Overlay Deployment in a Multi-cloud World -- MERCi-MIsS: Should I Turn off My Servers? -- Fully Distributed Privacy Preserving Mini-batch Gradient Descent Learning -- Incentivising Resource Sharing in Federated Clouds -- Similitude: Decentralised Adaptation in Large-Scale P2P Recommenders -- Concise Server-Wide Causality Management for Eventually Consistent Data Stores -- X-Ray: Monitoring and Analysis of Distributed Database Queries -- Dynamic Message Processing and Transactional Memory in the Actor Model -- Heterogeneous Resource Selection for Arbitrary HPC Applications in the Cloud -- Practical Evaluation of Large Scale Applications -- Cheap and Cheerful: Trading Speed and Quality for Scalable Social-Recommenders -- Replication of Recovery Log An Approach to Enhance SOA Reliability -- Leader Election Using NewSQL Database Systems -- Distributed Monitoring and Management of Exascale Systems in the Argo Project -- The Impact of Consistency on System Latency in Fault Tolerant Internet Computing -- A CRDT Supporting Selective Undo for Collaborative Text Editing -- Live Cloud Inspector: Towards Integrated IaaS Forensics in the Cloud.
Keywords: Computer Communication Networks; Computer system performance; Software engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Software Engineering/Programming and Operating Systems